Pengaruh Model Culturally Responsive Transformative Teaching terhadap Literasi Sains Peserta Didik - Desi Harianti; Saidil Mursali; Ismail Efendi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Students' low scientific literacy is evidenced by instruction that remains teacher-centered, a lack of connection between the material and real-life contexts or local culture, and suboptimal initial student proficiency (with pre-test averages of 52.00 for the experimental class and 52.75 for the control class). One alternative approach that can be implemented is the Culturally Responsive Transformative Teaching (CRTT) model based on Ngome local wisdom. This study aims to determine the effect of the Ngome-based CRTT model on students' scientific literacy regarding the topic of ecosystems. The study employed a quasi-experimental design, specifically a non-equivalent control group design. Data were collected via scientific literacy tests. The experimental class utilized the Ngome-based CRTT model, while the control class underwent conventional instruction. Data were analyzed using ANCOVA following the fulfillment of prerequisite analysis tests. The analysis results indicate that the CRTT model had a significant effect on students' scientific literacy, with a significance value of 0.000 (p < 0.05) and an F-value of 30.219. The average scientific literacy score in the experimental class rose from 52.00 to 84.25, whereas in the control class, it increased from 52.75 to 73.50. Thus, the Ngome-based CRTT model positively influences the improvement of students' scientific literacy regarding ecosystem material.